2020 Energy Balances - United Nations Department of Economic; Social Affairs (United Nations, 2023)
The 2020 Energy Balances contains energy balances for over 220 countries and territories, showing production, trade, transformation and consumption (by sector) in energy units for all energy products. It presents energy data for countries and areas in a format which shows the overall picture of the production, trade, transformation and consumption of energy products utilized in the region. Such a format is useful in assessing and analyzing supply and consumption patterns across both products and countries in detail on an internationally comparable basis.